Use of dried distillers grains with solubles and soybean hulls in nursery pig diets - F F Barbosa; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 3,186 pigs were used in two 21-d experiments to evaluate growth performance of nursery pigs fed different levels of dried distillers grains with soluble (DDGS) or soybean hulls. In each experiment, pigs (n = 1,593, and 24.0 lb in Exp. 1 and n = 1,593, and 27.3 lb in Exp. 2) were allotted to 72 pens (36 pens of barrows and 36 pens of gilts) with 21 or 22 pigs per pen on d 21 after weaning. A pen of barrows and pen of gilts shared a common feeder; thus, feeder was the experimental unit. In Exp. 1, treatments were a corn-soybean meal-based control diet or the same diet with 7.5, 15, or 22.5% added DDGS. Increasing DDGS from 0 to 22.5% did not affect ADG (P>0.26) or ADFI (P>0.21) but linearly (P<0.004) improved F/G. The survival rate of pigs (99.0 to 99.5%) was not affected (P>0.60) by diet. In Exp. 2, treatments were arranged as a 2 × 2 factorial with either 0 or 15% DDGS and 0 or 4% soybean hulls. Adding DDGS, soybean hulls, or the combination of DDGS and soybean hulls to the control diet did not affect (P>0.17) ADG. There was an interaction (P<0.01) between DDGS and soybean hulls for ADFI and a trend for an interaction (P<0.09) for F/G. Adding DDGS reduced ADFI and improved (P<0.04) F/G to a greater extent when added to the control diet than when added to the diet containing soy-bean hulls. Adding soybean hulls to the control diet did not affect (P>0.17) pig performance. The survival rate of pigs (99.5 to 100%) was not affected (P>0.31) by treatments. In summary, 15 to 22.5% DDGS and up to 4% soybean hulls were added to diets for 25- to 50-lb pigs without affecting ADG; increasing levels of DDGS (up to 22.5%) improved feed efficiency in these experiments.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Dried distillers grains with solubles; Nursery pig; Soybean hulls; Swine